Study and mitigation measures for the effects of stresses and vibrodynamic forces on rails resulting from the movement of freight train wheels (Международный научный журнал «Инженер», 2026)
All over the world the demand for railway transport of goods and passengers is increasing, which is the reasonfor increasing the requirements for all railway facilities. Every sphere of railway facilities is developing, newtechniques and technologies are being introduced, but despite such changes and developments, the railway hasnot yet escaped from technical difficulties and defects that lead to faulty conditions. The occurrence of trackdefects and defects in the junction zone on the sections with high-speed and heavy-weight train traffic,deterioration of track geometry, destruction of track rigidity, occurrence of faults under the influence ofvarious factors are also important with the increase of vibrodynamic actions and vibrations. So, the abovementionedaspects are put forward as the main problems to be reduced, the causes of these deficiencies, faultsand effects and the measures to eliminate and reduce them are given in this article.